IMPROVEMENT OF ANALYTICAL OPERATIONS USED IN THE AUDIT OF PRODUCTION PROCESSES IN ENTITY - Kahharova Ezoza Kahramon qizi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article examines the analytical operations used in the audit of production processes in economic entities. As a result of the research, proposals were developed on the implementation of analytical procedures used in the audit of production processes based on international standards.